PENGARUH IKLIM ORGANISASI TERHADAP DISIPLIN KERJA PEGAWAI DI DINAS PENDIDIKAN KOTA CIREBON - Adinda Afiah Syahda, - (2022)
This study aims to determine the influence of organizational climate on the work discipline of employees in the Cirebon City Education Office. The research approach used is descriptive research with a quantitative approach. The population of this study was 144 employees of the Cirebon City Education Office. The sample was calculated using a formula according to Akdon and Sahlan which was based on a 10% error rate of 64 employees. The normality test is carried out using the formula of Kolmogorov Smirnov. Calculations are processed using the SPSS program version 26.0 for Windows. The results of data processing a correlation coefficient of 0.511, which means that the Organizational Climate has a fairly strong correlation or relationship with Employee Work Discipline. The coefficient of determination was obtained at 26.1%, meaning that Employee Work Discipline was determined by the Organizational Climate of 26.1% and the remaining 73.9% was determined by other factors that were not variables of this study. The results of the regression equation provide an illustration of the dependence between Employee Work Discipline on the Organizational Climate and the regression equation Ŷ = 24.632 + 0.508X. That is, if the organizational climate increases by one unit, it will be followed by an increase in staffing discipline by 0.508. This study can be concluded that the organizational climate can have a positive and significant effect with a coefficient of determination of 26.1% on employee work discipline, and the rest is determined by other factors. The results of this study are expected to be used as input, lessons and references for subsequent researchers by looking at other factors such as the influence of leadership, job satisfaction, work motivation, and others.